The Cu/ligand stoichiometry effect on the coordination behavior of aroyl hydrazone with copper(II): Structure, anticancer activity and anticancer mechanism. Issue 10 (15th May 2016) - Deng, JunGang; Gou, Yi; Chen, Wei; Fu, Xiang; Deng, Hang
Graphical abstract: Abstract: In an effort to better understand the biological efficacy of the tridentate aroyl hydrazone Cu(II) complexes, three Cu(II) complexes of acetylpyridine benzoyl hydrazone (HL), [Cu(L)(NO3 ) (H2 O)]·H2 O (C1 ), [Cu(L)2 ] (C2 ) and [Cu(L)(HL)]·(NO3 )(Sas) (C3 ) (Sas = salicylic acid) were synthesized and characterized. X-ray crystal structures and infrared (IR) spectra of the complexes reveal that the L − ligand ofC1 andC2 are predominantly in the enolate resonance form, while one L − ligand inC3 is represented enolate resonance form and the other HL ligand exhibits keto resonance form. All Cu(II) complexes showed significantly more anticancer activity than the ligand alone. Interestingly, the Cu complexes where the ligand/metal ratio was 1:1 (C1 ) rather than 2:1 (C2 andC3 ) had higher antitumor efficacy. Moreover, the 1:1 Cu/ligand complex, C1, promotes A549 cell apoptosis possibly through the intrinsic reactive oxygen species (ROS) mediated mitochondrial pathway, accompanied by the regulation of Bcl-2 family proteins.